TECHNOLOGICAL INNOVATION AND BUSINESS RESILIENCE AMONG COSMETICS MANUFACTURING FIRMS IN SOUTH-EAST NIGERIA - Nwokorie, Peterson Chibuzo (African Journal of Social and Behavioural Sciences, 2025)
This article examines the role of technological innovation in enhancing business resilience among cosmetics manufacturers in Southeastern Nigeria. The Nigerian cosmetics industry is experiencing substantial growth, driven by a rising middle class, increasing urbanization, and the impact of social media. To proceed with the study, a sample of 148 senior and management staff from 8 selected cosmetics firms was studied. The study employed a survey research design, with the questionnaire serving as the primary instrument for data collection. The data collected were presented in tables and analyzed using simple percentages, bar charts, mean statistics, and Pearson correlation statistics, all of which were facilitated by SPSS version 21.0. Findings reveal a significant association between technological innovation and operational continuity, with a mean of 3.4; a significant relationship between technological innovation and employee engagement, with a mean of 3.4; and a significant relationship between technological innovation and customer retention, with a mean of 3.1. The study concludes that achieving business resilience depends on the extent of technological innovation implemented. It was recommended that: (1) production firms, especially cosmetics firms, should always involve innovative technology to achieve excellence, especially in today’s digital age. (2) Employees should be trained, developed, and engaged on the best ways to operate modern technologies in the company. (3) Modern production equipment should be used to achieve production of quality products, which will enhance customer attraction, patronage, and customer retention. (4) On their own, the Government should provide financial incentives, tax breaks, and grants to encourage manufacturers to invest in technology. Infrastructure development: Investing in improving electricity supply, transportation networks, and internet connectivity in south-east Nigeria.